Break point : two Minnesota athletes and the road to Title IX - Brenden, Sheri, 1959- (University of Minnesota Press, 2022)
"Break Point tells the story of how two Minnesota teenagers took on the inequitable system of high school athletics, setting a legal precedent for schools nationwide before the passage of Title IX. This scrupulously reported book is at heart the story of the girls whose pluck and determination--and heartache--led to a victory much greater than any high school championship"--